Clerodendrum volubile Ethanol Leaf Extract: A Potential Antidote to Doxorubicin-Induced Cardiotoxicity in Rats - Olufunke Esan Olorundare; Adejuwon Adewale Adeneye; Akinyele Olubiyi Akinsola; Daniel Ayodele Sanni; Mamoru Koketsu; Hasan Mukhtar (Journal of Toxicology, 2020)
Doxorubicin is widely applied in hematological and solid tumor treatment but limited by its off-target cardiotoxicity. Thus, cardioprotective potential and mechanism(s) of CVE in DOX-induced cardiotoxicity were investigated using cardiac and oxidative stress markers and histopathological endpoints. 50–400 mg/kg/day CVE in 5% DMSO in distilled water were investigated in Wistar rats intraperitoneally injected with 2.5 mg/kg DOX on alternate days for 14 days, using serum troponin I and LDH, complete lipid profile, cardiac tissue oxidative stress marker assays, and histopathological examination of DOX-treated cardiac tissue. Preliminary qualitative and quantitative assays of CVE’s secondary metabolites were also conducted. Phytochemical analyses revealed the presence of flavonoids (34.79 ± 0.37 mg/100 mg dry extract), alkaloids (36.73 ± 0.27 mg/100 mg dry extract), reducing sugars (07.78 ± 0.09 mg/100 mg dry extract), and cardiac glycosides (24.55 ± 0.12 mg/100 mg dry extract). 50–400 mg/kg/day CVE significantly attenuated increases in the serum LDH and troponin I levels. Similarly, the CVE dose unrelatedly decreased serum TG and VLDL-c levels without significant alterations in the serum TC, HDL-c, and LDL-c levels. Also, CVE profoundly attenuated alterations in the cardiac tissue oxidative stress markers’ activities while improving DOX-associated cardiac histological lesions that were possibly mediated via free radical scavenging and/or antioxidant mechanisms. Overall, CVE may play a significant therapeutic role in the management of DOX-induced cardiotoxicity in humans.